CASE REPORT: SURGICAL MANAGEMENT OF LUMBAR COMPRESSION FRACTURE - Yustinus Robby Budiman Gondowardojo; Tjokorda Gde Bagus Mahadewa (Neurologico Spinale Medico Chirurgico, 2018)
The lumbar vertebrae are the most common site for fracture incident because of its high mobility. The spinal cord injury usually happened as a result of a direct traumatic blow to the spine causing fractured and compressed spinal cord. A 38-year-old man presented with lumbar spine’s compression fracture at L2 level. In this patient, decompression laminectomy, stabilization, and fusion were done by posterior approach. The operation was successful, according to the X-Ray and patient’s early mobilization. Pneumothorax of the right lung and pleural effusion of the left lung occurred in this patient, so consultation was made to a cardiothoracic surgeon. Chest tube and WSD insertion were performed to treat the comorbidities. Although the patient had multiple trauma that threat a patient’s life, the management was done quickly, so the problems could be solved thus saving the patient’s life. After two months follow up, the patient could already walk and do daily activities independently.